The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.7554/elife.66738
|View full text |Cite
|
Sign up to set email alerts
|

Subventricular zone/white matter microglia reconstitute the empty adult microglial niche in a dynamic wave

Abstract: Microglia, the brain's resident myeloid cells, play central roles in brain defense, homeostasis, and disease. Using a prolonged colony-stimulating factor 1 receptor inhibitor (CSF1Ri) approach, we report an unprecedented level of microglial depletion and establish a model system that achieves an empty microglial niche in the adult brain. We identify a myeloid cell that migrates from the subventricular zone and associated white matter areas. Following CSF1Ri, these amoeboid cells migrate radially and tangential… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 110 publications
4
15
0
Order By: Relevance
“…Following unilateral transplantation, we observed partial microglial repopulation emanating from the injection site and the appearance of ''wavefronts'' of proliferative Ki67 + microglia adjacent to unoccupied regions of the brain (Figures 3H-3N). These wavefronts appear to be highly similar to those recently described during microglial repopulation following complete pharmacological depletion (Hohsfield et al, 2021). Thus, WT microglia appear capable of repopulating the entire brain of FIRE mice within 3 months.…”
Section: Ad Mice That Genetically Lack Microglia Exhibit Premature Le...supporting
confidence: 78%
“…Following unilateral transplantation, we observed partial microglial repopulation emanating from the injection site and the appearance of ''wavefronts'' of proliferative Ki67 + microglia adjacent to unoccupied regions of the brain (Figures 3H-3N). These wavefronts appear to be highly similar to those recently described during microglial repopulation following complete pharmacological depletion (Hohsfield et al, 2021). Thus, WT microglia appear capable of repopulating the entire brain of FIRE mice within 3 months.…”
Section: Ad Mice That Genetically Lack Microglia Exhibit Premature Le...supporting
confidence: 78%
“…Here, we identify specific remodeling states of microglia that persist following CSF1R inhibition showing reduced homeostatic gene expression. Other groups recently found small populations of CSF1R-independent or repopulating microglia in the brain, and we note similar patterns of gene expression, with reduced homeostatic genes such as Tmem119 and P2ry12 , and increased expression of genes such as Lyz2 ( Zhan et al, 2020 ; Hohsfield et al, 2021 ). In these microglia repopulation studies, it was proposed that more immature microglia survive CSF1R inhibition, but microglia maturation may not be a key factor in the context of development since we previously found greater dependence of retinal microglia on CSF1R at embryonic stages ( Anderson et al, 2019b ) than in postnatal retina ( Anderson et al, 2019a ).…”
Section: Discussionsupporting
confidence: 84%
“…Along with the hippocampus, the SVZ is a well-known niche for adult neurogenesis [ 140 , 141 , 142 ]. Due to its specific function in the brain, recent studies showed that a particular subpopulation of microglia might be involved in SVZ-specific neurogenesis [ 53 , 143 , 144 ]. One study demonstrated that microglia with a discrete morphology, such as having an amoeboid-like form and shorter branches, mediate SVZ neurogenesis [ 143 ].…”
Section: Intra- and Inter-regional Heterogeneity Of Astrocytes And Mi...mentioning
confidence: 99%